Network Pharmacology and Experimental Validation of the Therapeutic Effect of Baji Capsule on LPS-Induced Osteoporosis - Li Q; Li D; Tian C; Liu X; Wang H; Liu H (Orthopedic Research and Reviews)
Qian Li,1 Dinglin Li,1 Ciqiu Tian,2 Xiangjie Liu,1 Hui Wang,1 Hao Liu1 1Liyuan Hospital Affiliated to Tongji Medical College of Huazhong University of Science and Technology, Tongji Medical College of Science and Technology, Wuhan, People’s Republic of China; 2Hubei University of Chinese Medicine, Wuhan, People’s Republic of ChinaCorrespondence: Hao Liu, Liyuan Hospital affiliated to Tongji Medical College of Huazhong University of Science and Technology, Tongji Medical College of Science and Technology, Wuhan, People’s Republic of China, Email 729481937@qq.comPurpose: Osteoporosis is a common skeletal disease characterized by impaired bone microarchitecture, decreased bone mineral density and increased bone fragility, leading to a heavy physical and economic burden due to its greatly increased risk of fracture. Baji capsule is a proprietary medicine that can treat menstrual disorders and postmenopausal osteoporosis. However, the efficacy of Baji capsule has not been reported for osteoporosis caused by oxidative stress and inflammation. Therefore, the aim of this study was to evaluate whether Baji capsule has a therapeutic effect on lipopolysaccharide (LPS)-induced inflammatory osteoporosis and to explore the underlying mechanisms through network pharmacology.Patients and Methods: Osteoporosis model in ICR mice induced with LPS. Mice were treated with vitamin E (100mg/kg), PBS, high-dose Baji capsule (810mg/kg) and low-dose Baji capsule (90mg/kg), respectively. The therapeutic effect of Baji capsule was evaluated by high-resolution micro-computed tomography (Micro-CT) and tissue section staining, serum inflammatory factor levels were assessed by ELISA, serum oxidative stress-related marker levels were determined by kits, and finally the mechanism was explored by network pharmacology and then verified by immunohistochemistry.Results: Micro-CT results showed that Baji capsule attenuated LPS-induced inflammatory bone loss.Baji capsule also reduced serum inflammatory factor levels and oxygen free radical production. Target screening by network pharmacology yielded a total of 236 active ingredients of Baji capsule, as well as 278 common targets after taking the intersection of Baji capsule active ingredient targets and osteoporosis disease-related targets.Conclusion: Baji capsule can treat osteoporosis by reducing inflammation and oxidative stress. The therapeutic effects of Baji capsule were shown to be multi-targeted and multi-pathway through network pharmacology. In the future, its anti-inflammatory and antioxidant properties can be utilized to further explore its therapeutic effects on inflammatory diseases, as well as a prospective study for the clinical treatment of osteoporosis.Keywords: inflammatory, oxidative stress, osteoporosis, traditional Chinese medicine, network pharmacology